Intercountry Adoption in New Zealand - A Child Rights Perspective - Couchman, J (Victoria University of Wellington Law Review, 1997)
In 1996, the Adoption Amendment Bill (No 2) was introduced into Parliament. The aim of the Bill was to implement in New Zealand the Hague Convention on Protection of Children and Co-operation in Respect of Intercountry Adoption. New Zealand’s accession to the Hague Convention would provide significantly improved protection for some children who come to New Zealand as a result of intercountry adoption. This article provides information on intercountry adoption in New Zealand, the background to the Bill, and concludes that the Bill, if passed in its current form, would fail to provide protection for the majority of children who come to New Zealand as a result of intercountry adoption, and would not fulfil New Zealand’s obligations concerning adoption under the United Nations Convention on the Rights of the Child.